H-shaped stacked patch antenna for dual band operation - Ansari J.A.; Singh P.; Dubey S.K.; Khan R.U.; Vishvakarma B.R. (My University, 2025)
Analysis of U-slot loaded patch stacked with H-shaped parasitic elements is given in this paper. It is found that the antenna exhibits dual resonance and both the resonance frequency (upper and lower) depends directly on slot width and inversely on slot length. Both upper and lower resonance frequency increase with increasing the value of h2. Typically the bandwidth at lower and upper resonance is found 3.66% and 10.25% respectively. The radiated power at higher frequency (beamwidth 64?) is 0.73 dBas compared to lower resonance frequency (beamwidth 71?). The theoretical results are compared with the simulated data obtained from IE3D. © 2008, Electromagnetics Academy.